Impairment of quality of life among adults with skin disease in King Fahad Medical City, Saudi Arabia - Ibrahim A Al-Hoqail (Wolters Kluwer Medknow Publications, 2009)
Objectives: The objective of the study was to assess the quality of life in patients with skin disease. Subjects and Methods: A 6-month cross-sectional study was conducted in the Dermatology Clinic at King Fahad Medical City, Riyadh, Kingdom of Saudi Arabia. The study sample consisted of all 297 adult patients with dermatological conditions attending clinic but without associated psychiatric disease. They completed a self-administered Arabic version of the Dermatology Life Quality Index questionnaire (DLQI), containing ten items. The data was analyzed according to disease, age and gender. Results: The gender distribution of the study sample was 73% female and 27% male. The mean age was 29.4 years. The proportions of patients with various diagnoses were: sebaceous and apocrine gland disorders 31.3%, eczematous dermatitis 18.5%, cutaneous infections 13.5%, and pigmentary disorders 10.8%. The mean DLQI of all patients was 8.32. Patients with papulosquamous disorders recorded the highest mean DLQI score of 15.28, followed by immunological disorders with 11.11, eczematous dermatitis with 9.55, and miscellaneous disorders with 10.91. The mean DLQI was higher among females (9.02) than males (6.46). Age had no influence on the degree of impairment. Conclusion: Measuring the impairment of the quality of life in dermatology patients is an important aspect of management. It allows clinicians to assess the extent and nature of the disability so that an appropriate management regimen can be implemented and its effectiveness assessed.